Annual Plan 2005-2006 (Volume-I) National Capital Territory of Delhi - Planning Commission (Planning Commission, 2005)
For administrative convenience and development purposes, the entire rural area is divided into five development Blocks viz. Alipur, Kanjhawala, Najafgarh, Mehrauli and Shahdara. To make the administration more effective and accessible to the common man, the administrative machinery has been decentralized and divided into 9 Districts. Each District is headed by a Deputy Commissioner. Civic amenities are being provided by three local bodies viz.
Planning Department, Government of National Capital Territory of Delhi